A cross sectional study on community understanding of battery waste impact in Vojvodina - Čugalj Jovana; Vujić Bogdana; Batinic Bojan (Reciklaža i Održivi Razvoj)
The issue of waste batteries as a specific type of waste poses a major challenge to the environment, mainly due to improper disposal practices among the local population. The aim of this study is to explore the local population's awareness of the environmental impact of waste batteries, which are often discarded with regular waste instead of being disposed of properly. Although 67 % of respondents express concern about the ecological consequences, 69.63 % of respondents still dispose of used batteries improperly and only 32 % feel sufficiently informed about the environmental risks. The findings highlight the urgent need for targeted education initiatives to raise public awareness of proper disposal methods and the harmful effects of poor waste management on environmental health. The study also highlights the importance of promoting rechargeable batteries and developing accessible collection points to encourage proper disposal. Collaboration with local authorities and alignment with EU regulations are essential for the introduction of sustainable waste management practices.